Pendampingan Pembuatan Pupuk Organik Cair Bagi Warga Mangunsari Gunungpati Untuk Mengelola Taman TOGA Organik (BERDAYA Indonesian Journal of Community Empowerment, 2021)
In line with the clean and healthy lifestyle program (CHLP) that continues to be implemented in the Mangunsari area, Gunungpati District, the development of the TOGA garden in every dasawisma in the sub-district is also being carried out. The Mangunsari area has an area of ​​public facilities that have not been used intensively, so the potential to be used as a TOGA park is still very high. Mangunsari residents also have the potential to be empowered in managing an organic "Taman TOGA" with the application of biotechnology to make liquid organic fertilizer (LOF). This biotechnology can also utilize household organic waste. The purpose of this service activity is to empower members of RT 4 RW 5 Mangunsari Gunungpati District in applying biotechnology by utilizing household waste into LOF, as well as managing organic TOGA gardens using LOF. To achieve this goal, mentoring methods are used on how to make LOF from household organic waste, as well as assistance on how to care for and manage an organic TOGA garden with LOF. The results of the service showed an increase in participants' understanding of the importance of managing household waste into solid compost and LOF. Participants also understand the uses and advantages also methods of making LOF (100%), the quality of LOF (85%), manufacture and components of MOL (85-95%). In addition to understanding these concepts, the participants were very enthusiastic about making LOF and solid compost in groups per decade and used to manage the TOGA garden